Bochdalek hernia with liver herniation. Issue 3 (3rd March 2022) - Kanatani, Mao; Taniguchi, Hirokazu; Kusabiraki, Kimiho; Masaki, Yasuaki; Tsuda, Takeshi; Abo, Hitoshi
Abstract: Bochdalek hernia with liver herniation is rare and mimics a pulmonary mass. This case was hospitalized for masses found in the lower field of the right lung on a chest radiograph. The patient was diagnosed with Bochdalek hernia with liver herniation with three‐dimensional images created from thoracoabdominal‐enhanced computed tomography. Abstract : This manuscript provides an important three‐dimensional (3D) image of a rare case of Bochdalek hernia with liver herniation. 3D images are useful for the diagnosis of this condition.